Предмет: Алгебра,
автор: lizasharova17
6(-2х + 3) - 2(6x - 9) = -22 +5х.
Ответы
Автор ответа:
1
Ответ:
-12х+18-12х+18=-22+5х
-24х+36=-22+5х
-24х-5х=-22-36
-29х=-58
х=-58÷(-29)
х=2
Автор ответа:
1
Ответ:
вот ответ пожалуйста
Объяснение:
ты используешь перенос неизвестного на одну сторону а известные в другую
Приложения:
Похожие вопросы
Предмет: Математика,
автор: nika20051103melnik
Предмет: История,
автор: Аноним
Предмет: География,
автор: misha091126
Предмет: Математика,
автор: svetlanadudnicenko1
Предмет: История,
автор: 08julia26